Friendship in the Merovingian Kingdoms Venantius Fortunatus and His Contemporaries. - Williard, Hope (CARMEN monographs and studies., 2022)
Explores how one early medieval poet survived and thrived amidst the political turbulence of sixth-century Merovingian Gaul, and how the language of friendship shaped beliefs and behaviours, leading to social cohesion even within kingdoms repeatedly wracked by civil wars.